2021
DOI: 10.1149/1945-7111/ac24bb
|View full text |Cite
|
Sign up to set email alerts
|

Increased Moisture Uptake of NCM622 Cathodes after Calendering due to Particle Breakage

Abstract: As moisture presents a critical contamination in lithium-ion batteries (LIBs), electrodes and separators need to be post-dried before cell assembly. The moisture adsorption, desorption and re-adsorption of electrodes during processing is strongly dependent on their material system, manufacturing route and microstructure. The microstructure, in turn, is significantly defined by the coating density, which is adjusted by calendering. As a consequence, the calendering step is expected to directly influence the moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 54 publications
4
59
0
Order By: Relevance
“…However, particle breakage or fractioning in the cause of calendering is reported in the literature and may also be an origin for plastic deformation besides particle rearrangement. [ 12,15,31 ] As Figure 5a shows for higher mass loadings, higher maximum densities are reached, starting from ρ C = 3.18 g cm −3 for 200 g m −2 up to 3.41 g cm −3 for 350 g m −2 .…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…However, particle breakage or fractioning in the cause of calendering is reported in the literature and may also be an origin for plastic deformation besides particle rearrangement. [ 12,15,31 ] As Figure 5a shows for higher mass loadings, higher maximum densities are reached, starting from ρ C = 3.18 g cm −3 for 200 g m −2 up to 3.41 g cm −3 for 350 g m −2 .…”
Section: Resultsmentioning
confidence: 86%
“…However, applying high load during compaction may lead to the appearance of particle cracks, causing accelerated cell aging, as reported for LMO [12] and NMC. [13,14] Huttner et al [15] observed an increased moisture uptake for NMC622-based cathodes with higher electrode density and addressed this behavior to a rising surface area caused by particle breakage through higher calendering forces. Bockholt et al [13] also examined the correlation between the mixing and calendering process, showing improved capacity retention for electrodes with an intensive dry-mixing process route.…”
Section: Introductionmentioning
confidence: 99%
“…One aspect may be the fact that the SE cannot fill the pores of the primary particles within the polycrystalline active material. Moreover, high pressures during compaction can cause a breakage of the polycrystalline material [93,104] . As mentioned before, the higher surface of the single crystalline material can result in a higher degradation because of the larger contact area to the electrolyte.…”
Section: Processing At Laboratory Scalementioning
confidence: 98%
“…[ 116 ] The moisture content as an additional product parameter in combination with the coating density has been studied in the literature. [ 126 ] Figure 6 summarizes the parameters in the calendering process. It should be mentioned that, based on the defined reference process, the slitting process is followed after calendering and is not considered here.…”
Section: Literature‐based Prioritization Of the Parameters Based On T...mentioning
confidence: 99%
“…The surface finish is another property influenced by the calendering process. [118,125] Product parameters such as coating width, [118] mass loading, [119] coating density, [117] and the pore size distribution [126] are additional aspects that are considered in setting up the process parameters. Similar to the drying process, the quality of the electrode concerning common electrode defects, such as the camber effect, is another product parameter to be considered in the calendering process.…”
Section: Calendering Processmentioning
confidence: 99%